Phytochemical Analysis and Biological Activity of Hibiscus sabdariffa L. Extracts - Laaour Hadjer; Belkis Hamama (University of Eloued جامعة الوادي, 2025)
This study aims to evaluate the phytochemical content and biological activity of Hibiscus sabdariffa L. on four extracts using solvents of different polarities: hexane, butanol, ethanol, and water. Quantitative analyses were conducted to estimate the quantitative content of flavonoids, tannins, and total phenols in each extract, and we also performed biological activity tests to evaluate the plant's biological efficacy. The results showed that the ethanolic extract recorded the highest estimation in total phenolic content (186.3±30.20 mg GAE/g), while the butanolic extract excelled in flavonoids (63.3±0.87 μg QE/mg). The hexane extract recorded the highest estimation in terms of tannins (19.74±0.19 μg CE/mg). As for the biological activities, the ethanolic extract showed the best antioxidant activity according to the DPPH test (58.02±0.35 µg/mL), while the FRAP test recorded the strongest effectiveness of the aqueous extract. The ethanolic extract also recorded the highest (47.21±9.61) in the phosphomolybdic reductive capacity test. On the other hand, in the antihemolysis test, both the aqueous and ethanolic extracts showed the highest efficacy (~600 µg/mL) and in the anti-inflammatory test, while the ethanolic extract (15.94±1.22) exhibited the highest sun protection factor (SPF). These results clearly demonstrate the significant impact of solvent type on the extraction of biologically active compounds, and confirm that the ethanolic and butanolic extracts are the most effective options in terms of chemical content and biological activity.
Keywords: Hibiscus sabdariffa L.; plant extracts; phenolics; flavonoids; antioxidant activity; SPF; DPPH; FRAP; anti-inflammatory; anti-hemolysis.